2018
DOI: 10.1074/jbc.m117.791145
|View full text |Cite
|
Sign up to set email alerts
|

Low-level overexpression of p53 promotes warfarin-induced calcification of porcine aortic valve interstitial cells by activating Slug gene transcription

et al.

Abstract: The most frequently used oral anti-coagulant warfarin has been implicated in inducing calcification of aortic valve interstitial cells (AVICs), while the mechanism is not fully understood. The low-level activation of p53 is found to be involved in osteogenic transdifferentiation and calcification of AVICs. Whether p53 participating in warfarin-induced AVIC calcification remains unknown. In this study, we investigated the role of low-level p53 overexpression in warfarin-induced porcine AVIC (pAVIC) calcificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
5
12
0
Order By: Relevance
“…In contrast to the role of C646 in cancer cells, our results showed that C646 plays a protective role in high calcium/high phosphate–induced apoptosis and upregulates the level of Bcl-2 in pAVICs. In our previous study, we found higher baseline levels of the tumor suppressor p53 in AVICs than in other cell types 22 . We speculate that C646 may have opposing effect in different cell and chromatin status contexts or that some AVIC-specific expressed proteins may hinder the proapoptotic effect of C646.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In contrast to the role of C646 in cancer cells, our results showed that C646 plays a protective role in high calcium/high phosphate–induced apoptosis and upregulates the level of Bcl-2 in pAVICs. In our previous study, we found higher baseline levels of the tumor suppressor p53 in AVICs than in other cell types 22 . We speculate that C646 may have opposing effect in different cell and chromatin status contexts or that some AVIC-specific expressed proteins may hinder the proapoptotic effect of C646.…”
Section: Discussionmentioning
confidence: 72%
“…Porcine aortic valve interstitial cells (pAVICs) were isolated by collagenase digestion, as previously described 22 and cultured in Dulbecco’s modified Eagle’s medium (Gibco; Thermo Fisher Scientific, Inc., Waltham, MA, USA) supplemented with 10% fetal bovine serum (ScienCell Research Laboratories, Inc., San Diego, CA, USA) and 1% penicillin-streptomycin. Normal cells from passages 3 to 5 were used for later experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Directionality of p53 regulation in valvular calcification remains complicated, as warfarin treatment induces p53 overexpression and calcification in VIC cultures and murine aortic valves via recruitment to the Slug promoter. (27) While further studies will be needed to delineate the mechanistic contributions of valvular EVs to p53 transcriptional regulation, our data determined a putative role for EVs in contributing to this aspect of calcific valve disease.…”
Section: Discussionmentioning
confidence: 76%
“…Unfortunately, attempts to further interrogate this network were stymied because many components of this pathway are not annotated in Galgal5 . However, although co‐expression of Snai2 and p53 was unexpected, it is not without precedent and was recently described for aortic valve interstitial cells in response to warfarin‐induced stress, and it may be noteworthy that these cells are endothelial in origin and similarly emerged from an EMT event (Gao et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…A similar situation occurs in ribosomopathies, wherein endogenous Snai2 fails to prevent p53‐mediated NC death. Moreover, p53 has been shown to bind and directly stimulate Snai2 transcription (Gao et al, ; Wu et al, ), and it is possible the elevated Snai2 represents a failed attempt to counteract this p53 increase.…”
Section: Discussionmentioning
confidence: 99%